Acetazolamide-responsive exercise-induced episodic ataxia associated with a novel homozygous DARS2 mutation. Issue 10 (11th July 2011) - Synofzik, Matthis; Schicks, Julia; Lindig, Tobias; Biskup, Saskia; Schmidt, Thorsten; Hansel, Jochen; Lehmann-Horn, Frank; Schöls, Ludger
Abstract : Background: Leukoencephalopathy with brain stem and spinal cord involvement and brain lactate elevation (LBSL) was recently shown to be caused by mutations in the DARS2 gene, encoding a mitochondrial aspartyl-tRNA synthetase. So far, affected individuals were invariably compound heterozygous for two mutations in DARS2, and drug treatments have remained elusive. Methods: Prospective 2-year follow-up of the natural history of the main presenting symptoms in a homozygous DARS2 mutation carrier, followed by a 60 day treatment with acetazolamide in two different doses and with two random treatment interruptions. Results: The patient presented with exercise-induced paroxysmal gait ataxia and areflexia as an atypical phenotype associated with a novel homozygous DARS2 mutation. These features showed an excellent dose-dependent, sustained treatment response to a carbonic anhydrase inhibitor. Pathogenic mutations in episodic ataxia genes were excluded, thus making it highly unlikely that this phenotype was because of episodic ataxia as a second disorder besides LBSL. Conclusions: This case demonstrates that DARS2 mutation homozygosity is not lethal, as suggested earlier, but compatible with a rather benign disease course. More importantly, it extends the phenotypic spectrum of LBSL and reveals that at least some DARS2 -associated phenotypic features might be readily treatable. However, future observations of paroxsymal ataxia and, possibly, areflexia in other DARS2 -mutated patients are warranted to further corroborate our finding that DARS2 mutations can lead to a paroxsymal ataxia phenotype.